Reactive oxygen species and antioxidant system in selected skin disorders - Md. Jaffri, Juliana (Penerbit Universiti Sains Malaysia, 2023)
The skin has a solid protective system that includes the stratum corneum as the primary barrier and a complete antioxidant defence system to maintain the skin’s normal redox homeostasis. The epidermal and dermal cells are continuously exposed to physiological levels of reactive oxygen species (ROS) originating from cellular metabolic activities. Environmental insults, such as ultraviolet (UV) rays and air pollutants, also generate ROS that can contribute to structural damage of the skin. The antioxidant defence system ensures that the ROS level remains within the safe limit. In certain skin disorders, oxidative stress plays an important role, and there is an established interplay between oxidative stress and inflammation in the development of the condition. Lower levels of skin antioxidants indicate that oxidative stress may mediate the pathogenesis of the disorder. Accordingly, the total antioxidant level was also found to be lower in individuals with skin disorders in individuals with normal skin conditions. This review attempts to summarise the skin oxidant sources and antioxidant system. In addition, both skin and total antioxidant status of individuals with psoriasis, acne vulgaris, vitiligo and atopic dermatitis (AD), as well as their associations with the progression of these disorders will be reviewed.